Development of a dynamic food chain model for assessment of the radiological impact from radioactive releases to the aquatic environment. (July 2021) - de With, G.; Bezhenar, R.; Maderich, V.; Yevdin, Y.; Iosjpe, M.; Jung, K.T.; Qiao, F.; Perianez, R.
Abstract: The software tool POSEIDON-R was developed for modelling the concentration of radionuclides in water and sediments as well as uptake and fate in the aquatic environment and marine organisms. The software has been actively advanced in the aftermath of the Fukushima Dai-ichi accident. This includes development of an uptake model for the benthic food chain, a kinetic-allometric compartment model for fish and recent advancements for the application of 3 H. This work will focus on the food chain model development and its extension to key artificial radionuclides in radioecology such as 3 H. Subsequently, the model will be applied to assess the radiological dose for marine biota from 3 H, 90 Sr, 131 I, 134 Cs and 137 Cs released during and after the Fukushima Dai-ichi accident. The simulation results for 3 H, 90 Sr, 131 I, 134 Cs and 137 Cs obtained from the coastal box (4-4 km) located at the discharge area of the Fukushima Dai-ichi NPP, and the surrounding regional box (15–30 km) are compared with measurements. The predictions are by and large consistent with experimental findings, although good validation for 3 H, 90 Sr and 131 I is challenging due to lack of data. On the basis of the model predictions a dose assessment for pelagic and benthic fish is carried out. Maximum absorbed dose rates in the coastal box and the regional box are respectively 6000 and 50 μGy d −1 and are found in the pelagic non-piscivorous fish. Dose rates exceeding ICRP's derived consideration levels of 1 mGy d −1 are only found in the direct vicinity of the release and shortly after the accident. During the post-accidental phase absorbed dose rates consistently fall to levels where no deleterious effects to the marine biota are expected. The results also demonstrate the prolonged dose rate from 134 Cs and 137 Cs, particularly for benthic organisms, due to caesium's affinity with sediment, re-entry of caesium from the sediment into the food chain and external exposure from its high energetic gamma emissions. Uptake of non-organic tritium (HTO) and organically bound tritium (OBT) is modelled and shows some accumulation of OBT in the marine organism. However, dose rates from tritium, even during the accident, are low. Highlights: Development of POSEIDON-R's food chain model with extension for key radionuclides in radioecology. Predictions of 134 Cs, 137 Cs, 131 I, 90 Sr and 3 H in water, sediment, and aquatic organisms in agreement with observations. Dose rates near the FNPP discharge exceeded screening levels, but otherwise no deleterious effects to marine biota.